2011
DOI: 10.1002/cbf.1801
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of protein expression levels and DNA methylation status of breast cancer metastasis genes by anthracycline-based chemotherapy and the demethylating agent decitabine

Abstract: Epigenetic drugs are promising add-ons to cancer treatment; still, adverse effects concerning tumour promotion have been reported occasionally. In this in vitro study, we investigated the effect of combination treatment of decitabine with anthracycline-based chemotherapy [5-fluorouracil plus epirubicine plus cyclophosphamide (FEC)] on viability and metastatic activity of breast cancer cell lines, MDA-MB-231 (estrogen receptor-negative) and MCF-7 (estrogen receptor-positive). The effect of decitabine and its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…This suggests that in the MDA-MB-231 cells the apparent reduction in viability may be due to necrosis because of impaired apoptotic pathway(a). 86…”
Section: Epigenetics and Cancermentioning
confidence: 99%
“…This suggests that in the MDA-MB-231 cells the apparent reduction in viability may be due to necrosis because of impaired apoptotic pathway(a). 86…”
Section: Epigenetics and Cancermentioning
confidence: 99%
“…One possibility is that cancer or its treatment leads to epigenetic changes that predispose to chronic inflammation. Epigenetic alterations as a consequence of multiple chemotherapy regimens have been reported in numerous genes in DNA samples extracted from both breast cancer and peripheral blood cells (Ari et al, 2011; Avraham et al, 2012; Sharma et al, 2012; Swisher et al, 2009). However, the impact of chemotherapy-induced epigenetic changes has not been related to systemic inflammation and/or behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We found that in cells treated with decitabine, FEC, and the combination regimens, DAPK as well as TMS1 were significantly demethylated in the respective cell lines in a synergistic fashion. In addition, our previously data demonstrate that decitabine plus FEC treatments increased apoptosis than decitabine or FEC treatment alone in MCF-7 cells [38], which may be a result of reactivation of gene expression by promoter demethylation.…”
Section: Discussionmentioning
confidence: 81%
“…In our previous study, we show that the treatment of MCF-7 and MDA-MB-231 cells with FEC significantly reduced cell viability in a dose-dependent manner. However, the combination of the different doses of FEC with 10 µM decitabine did not impair cell viability levels any further [38].…”
Section: Discussionmentioning
confidence: 82%